Barriers and facilitators to the implementation of integrated community multimorbidity care model in Shanghai-a qualitative study based on normative process theory - SUI Mengyun1; FENG Jiachen1#; ZHANG Sheng1; CHENG Minna1; WANG Yuheng1; FU Chen1; SHI Yan1 (Yixue xinzhi zazhi)
Objective To analysis of the facilitators and barriers to the implementation of the integrated community multimorbidity care model from the perspective of the implementers, to bridge the implementation gap, and to provide policy recommendations for government.Methods A qualitative interview questionnaire was developed around the four constructs of normalisation process theory (NPT) (coherence, cognitive engagement, collective action and reflective monitoring) and 40 professionals from 11 community health centers in 10 administrative districts of Shanghai were interviewed, with data coded using NVivo 12 software.Results A total of 4 thematic terms and 11 sub-thematic terms were summarized as coherence (perceived value, understanding and implementing the purpose and vision of the model, new skills and requirements), cognitive engagement (implementers’ attitudes towards the new model, multi-sectoral engagement), collective action (current status of model implementation, team members’ cooperation and collaboration, resource support), reflective monitoring (data accessibility, sharing of implementation progress and effectiveness, population labelling and personalized alerts).Conclusion The model faces challenges in implementation such as unclear service objectives, irregular staffing, insufficient resource support, insufficient adhesion with family doctors, unavailability of relevant data, and low utilization of services, etc.It is recommended that clear objectives be set to increase recognition of the model, establish fixed posts and responsibilities for service providers, strengthen information disclosure and sharing between the authorities, the community, and within the team. Additionally, the utilization rates of voice follow-up and risk assessment should be improved, and standardized training for more specialized techniques should be provided to enhance data accessibility and utilization by implementers. Furthermore, an early warning system for patient cases should be established, along with grading the population, and government investment should be strengthened.